2012
DOI: 10.1007/s00704-012-0746-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent drought and precipitation tendencies in Ethiopia

Abstract: In 2011, drought in the Horn of Africa again made news headlines. This study aims to quantify the meteorological component of this and other drought episodes in Ethiopia since 1971. A monthly precipitation data set for 14 homogeneous rainfall zones was constructed based on 174 gauge observations. As a measure of drought, the Standardized Precipitation Index was calculated on seasonal, annual and biannual timescales for each zone. The results point to 2009 as a year of exceptionally widespread drought. All zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
285
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(342 citation statements)
references
References 45 publications
52
285
5
Order By: Relevance
“…Long-rain declines have been confirmed by many recent studies Liebmann et al, 2014;Lyon and DeWitt, 2012;Viste et al, 2012), and corroborated by analyses of normalized difference vegetation index imagery (Pricope et al, 2013) and satellite-observed soil moisture (Omondi et al, 2013 Nicholson (2014b). The source of the SST forcing behind these recent East African rainfall declines, however, continues to be a matter of considerable debate.…”
Section: Climate Change and Pacific Decadal Variability (Pdv)mentioning
confidence: 74%
“…Long-rain declines have been confirmed by many recent studies Liebmann et al, 2014;Lyon and DeWitt, 2012;Viste et al, 2012), and corroborated by analyses of normalized difference vegetation index imagery (Pricope et al, 2013) and satellite-observed soil moisture (Omondi et al, 2013 Nicholson (2014b). The source of the SST forcing behind these recent East African rainfall declines, however, continues to be a matter of considerable debate.…”
Section: Climate Change and Pacific Decadal Variability (Pdv)mentioning
confidence: 74%
“…Belg rain is also crucial for pasture. Most big droughts in Ethiopia are associated with dry Belg (Viste et al 2012). …”
Section: Study Areas: Raya Azebo and Kobo Districtsmentioning
confidence: 99%
“…Irrespective of the determinants of this variability, seasonal rainfall fluctuations notoriously and frequently lead to drought conditions in the region (Hastenrath et al 2007;Rojas et al 2011;Viste et al 2013) thereby affecting large numbers of households that predominantly depend on sufficient rainfall for sustaining their livelihoods.…”
Section: Introductionmentioning
confidence: 99%